Implementasi Konsep Kasih Pada Interior Rumah Kreatif Mawari - Natalia Natalia; Laksmi Kusuma Wardani; Lucky Basuki (Intra, 2019)
Education is an important factor in improving human resources. The lack of educational facilities for underprivileged children is one of the problems that always arise in big cities, especially in Surabaya. The Mawari Shelter Community is a form of social service for the GKI Pregolan church in Surabaya which provides free educational facilities for underprivileged children. For this reason, the purpose of the Mawari Creative Home Interior Design in Surabaya is for education, a place for social interaction, and a place to facilitate creative activities that can improve the economy in the community. This design uses the Design Thinking method, consisting of 6 stages, Empathize, Define, Ideate, Prototype, Test, Implement, and Materialize. The application concept of